Optimization of substrate-analogue furin inhibitors - Ivanova, Teodora; Kallis, Stephanie; Bartenschlager, Ralf (ChemMedChem, 2017)
The proprotein convertase furin is a potential target for drug design, especially for the inhibition of furin-dependent virus replication. All effective synthetic furin inhibitors identified thus far are multibasic compounds; the highest potency was found for our previously developed inhibitor 4-(guanidinomethyl)phenylacetyl-Arg-Tle-Arg-4-amidinobenzylamide (MI-1148). An initial study in mice revealed a narrow therapeutic range for this tetrabasic compound, while significantly reduced toxicity was observed for some tribasic analogues. This suggests that the toxicity depends at least to some extent on the overall multibasic character of this inhibitor. Therefore, in a first approach, the C-terminal benzamidine of MI-1148 was replaced by less basic P1 residues. Despite decreased potency, a few compounds still inhibit furin in the low nanomolar range, but display negligible efficacy in cells. In a second approach, the P2 arginine was replaced by lysine; compared to MI-1148, this furin inhibitor has slightly decreased potency, but exhibits similar antiviral activity against West Nile and Dengue virus in cell culture and decreased toxicity in mice. These results provide a promising starting point for the development of efficacious and well-tolerated furin inhibitors.
First published: 23 October 2017
Gesehen am 19.10.2018